2021
DOI: 10.18632/aging.203274
|View full text |Cite
|
Sign up to set email alerts
|

Albiflorin alleviates cognitive dysfunction in STZ-induced rats

Abstract: Background: To explore the effect of albiflorin (AL) on streptozotocin (STZ)-induced Alzheimer's disease (AD) in rats. Methods: A mouse model of diabetic encephalopathy was established by intraperitoneal injection of 1%STZ. Step down test and water maze test were used to test the cognitive function of rats. Congo Red Staining was used to detect the distribution of Aβ plaques in the hippocampus of rats. Cytokine levels in serum and hippocampus were measured using ELISA. Serum insulin, oral glucose to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Recent studies have proved that traditional Chinese medicine was efficient in relieving inflammatory response and GDM. For instance, puerarin treatment improved the expression of IRS-1, TLR4, MyD88, and NF-κB in GDM rats (Ma et al, 2021). Resveratrol treatment brought about improved maternal glucose and lipid homeostasis in both C57BL/KsJ-Lep (db/+) mouse and streptozotocin-induced diabetes animal model.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have proved that traditional Chinese medicine was efficient in relieving inflammatory response and GDM. For instance, puerarin treatment improved the expression of IRS-1, TLR4, MyD88, and NF-κB in GDM rats (Ma et al, 2021). Resveratrol treatment brought about improved maternal glucose and lipid homeostasis in both C57BL/KsJ-Lep (db/+) mouse and streptozotocin-induced diabetes animal model.…”
Section: Discussionmentioning
confidence: 96%
“…The reduced levels of ROS and MDA in the hippocampus were often reported as the consequent events. Interestingly, many studies also mentioned the inhibited NF-κB signaling in addition to the Nrf2-mediated antioxidant response [7,106,114]. The upregulated expression of HO-1 protein in response to the Nrf2 upregulation suppresses the NF-κB activation which governs the transcriptions and productions of proinflammatory cytokines.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Mounting epidemiological studies showed that the risk of cognitive decline in middle-aged diabetic patients was 2-3 times higher compared with healthy peers [5,6]. Moreover, the prevalence of cognitive impairment is predicted to increase dramatically in the future with a longer survival time for diabetic patients [7]. Cognitive decline among children with T1DM is mainly manifested as subtle changes in cognitive development, whereas adults present subtle decrements in cognitive performance compared to age-matched controls [8].…”
Section: Introductionmentioning
confidence: 99%
“…They can reduce neuroinflammatory reactions and regulate oxidative stress related reactions by regulating the autosecretory of nerve cells and the active factors secreted by glial cells. Albiflorin (AL) can reduce AD pathology and improve cognitive impairment by regulating oxidative stress and inflammation in the brain ( 18 ). Nobiletin(NOB) can regulate microglia and relieve neuroinflammation ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are rich in many TCMs. They can reduce (18). Nobiletin(NOB) can regulate microglia and relieve neuroinflammation (19).…”
mentioning
confidence: 99%